2014
DOI: 10.1002/chem.201402537
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Inhibitors for Carbohydrate‐Processing Enzymes: Beyond the “Lock‐and‐Key” Concept

Abstract: During the last decades, tremendous chemical efforts have been dedicated to design monovalent inhibitors of carbohydrate-processing enzymes, with comparatively few rewards in terms of marketed drugs. Recently, an alternative to the traditional "lock and key" approach has emerged. Multivalency, a widely used strategy for lectin inhibition, has been successfully applied to specific glycosidases and glycosyltransferases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 58 publications
(56 reference statements)
2
55
0
Order By: Relevance
“…Clustering of inhibitory moieties (inhitopes) on multivalent scaffolds has been shown to inhibit glycosidases with high potency. 1930 Use of the GlcNS(6S) α (1,4)GlcA disaccharide is also advantageous, as it does not contain an iduronic acid unit nor a C(3)-sulfated glucosamine, diminishing cross-bioactivity. 43,5962 Furthermore, we hypothesize that attachment of this disaccharide to the aglycon polymerizable linker, which disrupts the hydrolytic ability of heparanase and provides π -cation interactions if an aromatic system is employed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clustering of inhibitory moieties (inhitopes) on multivalent scaffolds has been shown to inhibit glycosidases with high potency. 1930 Use of the GlcNS(6S) α (1,4)GlcA disaccharide is also advantageous, as it does not contain an iduronic acid unit nor a C(3)-sulfated glucosamine, diminishing cross-bioactivity. 43,5962 Furthermore, we hypothesize that attachment of this disaccharide to the aglycon polymerizable linker, which disrupts the hydrolytic ability of heparanase and provides π -cation interactions if an aromatic system is employed.…”
Section: Resultsmentioning
confidence: 99%
“…However, to the best of our knowledge, the use of synthetic polymers have yet to be fully explored. 19,20,30 …”
Section: Introductionmentioning
confidence: 99%
“…54,55 It is reasonable to expect that the novel phenomenon uncovered here may not be limited solely to glyco-ND but likely manifested by other multivalent constructs based on alternate scaffolds, NP-based or otherwise. 54,55 It is reasonable to expect that the novel phenomenon uncovered here may not be limited solely to glyco-ND but likely manifested by other multivalent constructs based on alternate scaffolds, NP-based or otherwise.…”
Section: Discussionmentioning
confidence: 95%
“…[13][14] In the case of carbonic anhydrase, only studies on bivalent inhibitors were recently reported.I ndeed, Whiteside'sr esearch group describedi n2 012 the binding of monovalent and bivalent benzene sulfonamide ligandst oasynthetic dimer of carbonic anhydrase.…”
mentioning
confidence: 99%